ON DEFORMATION OF BENDING OF A BEAM SUBJECTED TO UNIFORMLY DISTRIBUTED LOAD - A K ALDABERGENOV (Structural Mechanics of Engineering Constructions and Buildings, 2015)
A method of integrating of a differential equation of the bended axis of a beam subjected to uniformly distributed load is presented in the paper. The universal equations of deformation of bending are obtained without introduction of any additional conditions and limitations. These equations coincide with the known equations of a method of initial parameters.